Concise synthesis of (-)-steviamine and analogues and their glycosidase inhibitory activities - Nadechanok Jiangseubchatveera (2018)
A concise synthesis of (-)-steviamine is reported along with the synthesis of its analogues 10-nor-steviamine, 10-nor-ent-steviamine and 5-epi-ent-steviamine. These compounds were tested against twelve glycosidases (at 143 μg mL < sup > -1 < /sup > concentrations) and were found to have in general poor inhibitory activity against most enzymes. The 10-nor analogues however, showed 50-54% inhibition of α-l-rhamnosidase from Penicillium decumbens while one of these, 10-nor-steviamine, showed 51% inhibition of N-acetyl-β-d-glucosaminidase (from Jack bean) at the same concentration (760 μM). © The Royal Society of Chemistry 2013.